Hydrolysis of raw fish proteins extracts by Carnobacterium maltaromaticum strains isolated from Argentinean freshwater fish - Dallagnol, Andrea Micaela (2021)
Lactic acid bacteria (LAB) isolated from freshwater fish (hatcheries and captures) from Paraná river (Argentina) were analyzed by using culture-dependent approaches. The species belonging to Carnobacterium (C.) divergens, C. inhibens, C. maltaromaticum, C. viridans and Vagococcus (V.) salmoninarum were identify as predominant by RAPD-PCR and 16 s rRNA gene sequencing. C. maltaromaticum (H-17, S-30, B-42 and S-44) grew in raw fish extract and slightly reduced the medium pH (5.81–5.91). These strains exhibited moderate fish sarcoplasmic protein degradation (≤ 73 %) releasing small peptides and free amino acids, being alanine, glycine, asparagine and arginine concentrations increased in a higher extent (17.84, 1.47, 1.26 and 0.47 mg/100 mL, respectively) by S-44 strain at 96 h incubation. Interestingly C. maltaromaticum H-17 was able to inhibit Listeria monocytogenes. Results suggest that these strains would contribute to the development of new safe and healthy fishery products with improved nutritional and sensory characteristics.